Correction: Kim et al. Spatial Correlations between Nitrogen Budgets and Surface Water and Groundwater Quality in Watersheds with Varied Land Covers. Agriculture 2024, 14, 429 - Deok-Woo Kim; Eu Gene Chung; Eun Hye Na; Youngseok Kim (Agriculture)
Missing Funding [...]